Prevalence and Dietary Management of Polycystic Ovary Syndrome among Libyan Women Attending Tripoli Infertility Center - Noor AL-Hoda Ben-Issa; Maysm Abofaed; Hend Alqeeyadi; Mohamed Alshahrani; Eshraq Alsherif (AlQalam Journal of Medical and Applied Sciences, 2024)
Polycystic ovarian syndrome (PCOS) is the most common heterogenic endocrine illness in women of reproductive age, caused mostly by an excess of androgen and ovarian dysfunction. The present study was carried out to estimate the prevalence of PCOS among Libyan women who attended infertility center Tripoli, Libya, from 2020-2022, evaluate hormonal profile, Body Mass Index, weight and west circumferential before and after treatment and diet management. A longitudinal cross-sectional study conducted in the Tripoli Fertility Center in Tripoli, Libya, the study population targeting output Libyan female patients who presented to the gynecology and obstetrics (OPD) department and therapeutic nutrition department. Data Retrospectively collected from 2020 until 2022 and diagnosed using Rotterdam’s criteria. A total of 603 patients visited the gynecology and obstetrics department and the therapeutic nutrition department between January 2020 and December 2022. Out of which 174 women in the PCOS group and 429 in the non-PCOS group. The prevalence of PCOS was 29.56% in 2020, 37.5% in 2021, and 20.27% in 2022. The mean age of PCOS was 34.90 ± 5.5 SD, and all of the PCOS group were married. Worth to mention that all of PCOS cases was insulin resistance type. In terms of weight in the PCOS group, 19.54% were obese BMI >29, 68.96% were morbid obese with BMI >35, and approximately 68.39% of waist circumference measurements were more than 88cm. Hirsutism and oligomenorrhea were the major clinical features, morbid obese seems to be more prevalent in Libyan PCOS patients, low carbohydrate diet and physical activities may play an important role in PCOS management. متلازمة المبيض المتعدد الكيسات هي أكثر أمراض الغدد الصماء غير المتجانسة شيوعًا لدى النساء في سن الإنجاب، وينجم معظمها عن زيادة الأندروجين وخلل في المبيض. أجريت هذه الدراسة لتقدير مدى انتشار متلازمة تكيس المبايض بين النساء الليبيات اللاتي راجعن مركز العقم طرابلس، ليبيا، من 2020-2022، وتقييم الملف الهرموني، ومؤشر كتلة الجسم، والوزن والكفافي الغربي قبل وبعد العلاج وإدارة النظام الغذائي. دراسة مقطعية طولية أجريت في مركز طرابلس للعقم في طرابلس، ليبيا، استهدف مجتمع الدراسة مخرجات المريضات الليبيات اللاتي قدمن إلى قسم أمراض النساء والتوليد وقسم التغذية العلاجية. تم جمع البيانات بأثر رجعي من عام 2020 حتى عام 2022 وتم تشخيصها باستخدام معايير روتردام. زار إجمالي 603 مريضة قسم أمراض النساء والتوليد وقسم التغذية العلاجية في الفترة ما بين يناير 2020 وديسمبر 2022. من بينهم 174 امرأة في مجموعة متلازمة تكيس المبايض و429 في مجموعة غير مصابة بمتلازمة تكيس المبايض. بلغ معدل انتشار متلازمة تكيس المبايض 29.56% في عام 2020، و37.5% في عام 2021، و20.27% في عام 2022. وكان متوسط عمر متلازمة تكيس المبايض 34.90 ± 5.5 SD، وكانت جميع مجموعة متلازمة تكيس المبايض متزوجات. ومن الجدير بالذكر أن جميع حالات متلازمة تكيس المبايض كانت من النوع المقاوم للأنسولين. من حيث الوزن في مجموعة متلازمة تكيس المبايض، كان 19.54% يعانون من السمنة المفرطة بمؤشر كتلة الجسم >29، و68.96% يعانون من السمنة المفرطة مع مؤشر كتلة الجسم >35، وحوالي 68.39% من قياسات محيط الخصر كانت أكثر من 88 سم. كانت الشعرانية وندرة الطمث من السمات السريرية الرئيسية، ويبدو أن السمنة المرضية أكثر انتشارًا في مرضى متلازمة تكيس المبايض الليبيين، وقد يلعب النظام الغذائي منخفض الكربوهيدرات والأنشطة البدنية دورًا مهمًا في إدارة متلازمة تكيس المبايض